Healthy lifestyles and risk of major non-communicable chronic diseases and mortality in individuals with metabolic syndrome - Xiang Gao; Jiali Zheng; Mengdan Liu; Chong Liu; Yixin Wang; Yan Li; Weihua Chen; Xiaoguang Li; Hui Wang (The Journal of Nutrition, Health and Aging)
Objectives: To assess the associations between lifestyle factors and the risk of non-communicable chronic diseases (NCDs) and mortality in individuals with metabolic syndrome (MS), and to evaluate population-attributable risk (PAR) from multiple lifestyle factors. Methods: The study included 49,891 MS individuals from the UK Biobank. Seven lifestyle factors (smoking, diet, physical activity, sedentary behavior, sleep duration, psychological stress, and social contact status) were assessed using both unweighted and weighted lifestyle scores. Cox proportional hazards model was used to analyze the associations between lifestyle factors and major NCDs (diabetes, cardiovascular disease [CVD], chronic obstructive pulmonary disease [COPD], chronic kidney disease [CKD], and cancer) and all-cause mortality. Results: During a median follow-up of 11.0 years, 19,435 major NCDs and 3,578 deaths were recorded. Higher adherence to healthy lifestyle factors, assessed by both unweighted and weighted scores, was significantly associated with lower risks of major NCDs and all-cause mortality. Compared with participants having 0−3 healthy lifestyle factors (unweighted score), those with 6−7 factors had 28% (HR = 0.72, 95% CI: 0.69−0.75) lower risk of major NCDs and 39% (HR = 0.61, 95% CI: 0.55−0.69) lower risk of mortality. Correspondingly, using the weighted lifestyle score, the very healthy group showed a 27% (HR = 0.73, 95% CI: 0.70−0.76) lower risk of major NCDs and a 40% (HR = 0.60, 95% CI: 0.54−0.66) lower risk of mortality compared with the very unhealthy group. The PARs associated with all 7 healthy lifestyle factors were 20.72% and 26.93% for major NCDs and all-cause mortality, respectively. Conclusions: The adoption of multiple healthy behaviors significantly reduces the risk of NCDs and mortality in MS patients, highlighting the need for more comprehensive lifestyle interventions targeted at this group with metabolic impairments.